Pengaruh Keseimbangan Terhadap Kelincahan Dalam Permainan Sepakbola Pada Pemain SSB Bajeng United Gowa - Arba', Muhammad Arkanul (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of balance on agility in soccer among SSB Bajeng United Gowa players. The research method used is a quantitative method with a correlational approach. The population in this study includes all 20 players of SSB Bajeng United Gowa. The sampling technique used total sampling so that the entire population was used as samples. The research was conducted at ROMANG Rappoa field, Bajeng District, Gowa Regency in January 2025. The instrument used to measure balance was the Stork Stand Test, while agility was measured using the Illinois Agility Test. Data analysis used normality test, linearity test, and simple linear regression test. The results showed that there is a significant influence of balance on the agility of SSB Bajeng United Gowa soccer players with a correlation value of r = 0.735 and a coefficient of determination R² = 0.540, which means that balance contributes 54% to agility. Based on the results of this study, it is recommended for coaches to provide special training that can improve players' balance in order to enhance their agility in playing soccer.